Case 3787: Rhyncholepta grandicallosa Bergroth, 1911 (Insecta, Hemiptera, Heteroptera): proposed replacement of the lectotype by a neotype - Kment, Petr; Eger, Joe E Jr; Rider, David A (Bulletin of Zoological Nomenclature, 2019)
The purpose of this application, under Article 75.5 of the Code, is to replace the unidentifiable female lectotype of the Neotropical shield bug Rhyncholepta grandicallosa Bergroth, 1911 (Pentatomidae, Pentatominae, Chlorocorini), with a recently collected male neotype from the type locality, French Guiana.
Keywords: Nomenclature; taxonomy; lectotype; neotype; Heteroptera; Pentatomidae; Rhyncholepta; Neotropical Region